Importancia global y local de la diabetes mellitus tipo 2 - Sandoval C., Marjorie (Revista Hospital Clínico Universidad de Chile, 2012)
The purpose of this paper is to report on the current situation of diabetes mellitus, in order to gauge the current pandemic to which we are confronted. Diabetes, especially type 2, is a disease that has increased in prevalence in recent decades. In 2011 there were more than 366 million people affected by diabetes worldwide (comparative prevalence of 8.5%). Of the diabetic patients, 90% have type 2. Currently, diabetes is considered a pandemic, being the most developed regions and developing countries the most affected. Although there is an increased prevalence in all age groups, the highest number of people affected by diabetes is in the group between 40 and 59 years; but, if you analyze the relative prevalence by age group, the adult population over 65 years had the highest prevalence, ordering 40%. In our country, the overall prevalence of diabetes more than doubled between 2003 and 2009: from 4.2 to 9.4%, partly due to the exaggerated increase in obesity, which is directly linked to the development of this pathology. In sum, the exaggerated increase in prevalence of this disease makes it to be considered as a public health problem, which requires public policies to improveits prevention and management.